The Timothy Pickering papers - Pickering, Timothy, 1745-1829 (Massachusetts Historical Society microfilm publication, 1966)
Family and general correspondence; business and legal papers concerning land speculations in the Wyoming Valley (Pa.), western Virginia, Stokes and Surry Counties, N.C., and the Potter Land Company; agricultural papers, papers (1786-1809) concerning Pickering's missions to the Indians; correspondence, official documents, and historical notebooks collected for a proposed history of the United States during the Revolution; political notebooks and journals; account books (1780-84) of the Quartermaster General's office; military papers; pamphlets; news clippings; legal papers (1777-99) of Pickering's son, Octavius Pickering; and papers of his sons, John and Henry Pickering and their families.